Quarantine and Isolation during COVID‐19 outbreak: A case of online diagnosis of supraventricular arrhythmia through telemedicine - Mattioli, Anna Vittoria; Ballerini Puviani, Matteo; Malagoli, Andrea (Journal of arrhythmia, 2020)
The present case report highlights the usefulness of telemedicine during quarantine and isolation. The patient developed a supraventricular arrhythmia, and the diagnosis and management of the arrhythmia was done online.